2019
DOI: 10.1063/1.5099576
|View full text |Cite
|
Sign up to set email alerts
|

Heusler interfaces—Opportunities beyond spintronics?

Abstract: Heusler compounds, in both cubic and hexagonal polymorphs, exhibit a remarkable range of electronic, magnetic, elastic, and topological properties, rivaling that of the transition metal oxides. To date, research on these quantum materials has focused primarily on bulk magnetic and thermoelectric properties or on applications in spintronics. More broadly, however, Heuslers provide a platform for discovery and manipulation of emergent properties at well-defined crystalline interfaces. Here, motivated by advances… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 239 publications
(355 reference statements)
0
13
0
Order By: Relevance
“…Density functional theory * jkawasaki@wisc.edu (DFT) calculations in the absence of on-site Coulomb repulsion predict a bandgap of 0.37 eV, larger than the ∼ 100 meV predicted for FeSi [15,16]. While FeVSb and other 18 electron half-Heuslers are promising materials for thermoelectric power conversion [17][18][19], Heusler compounds more broadly exhibit highly tunable topological states [20][21][22][23], magnetism [24][25][26], and novel superconductivity [27,28] as a function of electron count [29,30]. Here, using angle-resolved photoemission spectroscopy measurements, we reveal a mass enhancement of m * /m bare = 1.4 in epitaxial FeVSb films with respect to the DFT band mass m bare .…”
Section: Introductionmentioning
confidence: 99%
“…Density functional theory * jkawasaki@wisc.edu (DFT) calculations in the absence of on-site Coulomb repulsion predict a bandgap of 0.37 eV, larger than the ∼ 100 meV predicted for FeSi [15,16]. While FeVSb and other 18 electron half-Heuslers are promising materials for thermoelectric power conversion [17][18][19], Heusler compounds more broadly exhibit highly tunable topological states [20][21][22][23], magnetism [24][25][26], and novel superconductivity [27,28] as a function of electron count [29,30]. Here, using angle-resolved photoemission spectroscopy measurements, we reveal a mass enhancement of m * /m bare = 1.4 in epitaxial FeVSb films with respect to the DFT band mass m bare .…”
Section: Introductionmentioning
confidence: 99%
“…These alloys crystallize in cubic full-Heusler (X2YZ) and half-Heusler (XYZ) variants, incorporating a variety of X and Y transition metals (e.g., Mn, Fe, Co, Ru) and Z main group elements (e.g., Al, Si, Ga, Ge, In, Sn, Sb) [1,2]. Magnetic examples from this alloy class provide perfect illustrations of their diverse functionalities, which include: ferromagnetism with nonmagnetic X, Y, Z; high Curie temperature (TC) and saturation magnetization (MS); half-metallic or highly spin-polarized character; spin-gapless semiconducting behavior; magnetocaloric response; and exciting topological characteristics [1][2][3][4]. Particularly extensively studied in this context are NiMnSb and the Co2MnZ and Ni2MnZ families, although interest has been widespread [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic examples from this alloy class provide perfect illustrations of their diverse functionalities, which include: ferromagnetism with nonmagnetic X, Y, Z; high Curie temperature (TC) and saturation magnetization (MS); half-metallic or highly spin-polarized character; spin-gapless semiconducting behavior; magnetocaloric response; and exciting topological characteristics [1][2][3][4]. Particularly extensively studied in this context are NiMnSb and the Co2MnZ and Ni2MnZ families, although interest has been widespread [1][2][3][4]. A pervasive strategy in the investigation of such materials is to study quaternary solid solution or deliberately off-stoichiometric versions, such as Co2FeGe1-xGax, Ni2Mn1+xSn1-x, etc., which enable composition-based tuning of lattice parameter, spinpolarized electronic structure, topological band structure, and so on [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it remains an outstanding challenge to control the stoichiometry to "electronicgrade" quality. For example, while the intrinsic carrier concentration of silicon is n i ∼ 10 10 cm −3 at room temperature, typical experimental carrier concentrations for semiconducting half Heuslers are typically ∼ 10 19 to 10 21 cm −3 due to defects and nonstoichiometry, which are difficult to control to better than 1% [21]. In select cases it has been shown that several Sb-containing Heuslersincluding CoTiSb [22,23], NiMnSb [24,25], LuPtSb [26], LaPtSb [27], and LaAuSb [28] -can be grown with an excess Sb flux, in which the ratio of Sb to (X + Y ) is self-limiting.…”
mentioning
confidence: 99%